Patient-level information and costing systems (PLICSs): a mixed-methods study of current practice and future potential for the NHS health economy - Sue Llewellyn; Naomi Chambers; Sheila Ellwood; Christos Begkos; Chris Wood (National Institute for Health Research, 2016)
Background: Traditionally, the cost object in health care has been either a service line (e.g. orthopaedics) or a clinical intervention (e.g. hip replacement). In the mid-2000s, the Department of Health recommended that in the future the patient should be the cost object, to enable a better analysis of cost drivers in health care, resulting in patient-level information and costing systems (PLICSs). Monitor (the economic regulator for health care) proposes that PLICS data will now form the basis for mandatory prices for health-care services across all care settings. Objective: Our main aim was to investigate the use of PLICSs. Methods: We surveyed all English foundation trusts and NHS trusts, and undertook four case studies of foundation trusts. Three trusts were generalist and one was specialist. We also surveyed commissioning support units to explore the potential for PLICSs in commissioning. Findings: The most significant use of PLICSs was cost improvement within the trusts. There was only modest utilisation of PLICSs to allocate resources across services and settings. We found that trusts had separate reporting systems for costs and clinical outcomes, engendering little use for PLICSs to link cost with quality. Although there was significant potential for PLICSs in commissioning, 74% of survey respondents at trusts considered their PLICS data to be commercially sensitive and only 5% shared the data with commissioners. The use of PLICSs in community services was, generally, embryonic because of the absence of units of health care for which payment can be made, service definitions and robust data collection systems. The lack of PLICS data for community services, allied with the commercial sensitivity issue, resulted in little PLICS presence in collaborative cross-organisational initiatives, whether between trusts or across acute and community services. PLICS data relate to activities along the patient pathway. Such costs make sense to clinicians. We found that PLICSs had created greater clinical engagement in resource management despite the fact that the trust finance function had actively communicated PLICSs as a new costing tool and often required its use in, for example, business cases for clinical investment. Operational financial management at the trusts was undertaken through service line reporting (SLR) and traditional directorate budgets. PLICSs were considered more of a strategic tool. Conclusions: Both PLICSs and SLR identify and interrogate service line profitability. Although trusts currently cross-subsidise to support loss-making areas under the tariff, they are actively considering disinvesting in unprofitable service lines. Financial pressure within the NHS, along with its current competitive, business-oriented ethos, induces trusts to act in their own interests rather than those of the whole health economy. However, many policy commentators suggest that care integration is needed to improve patient care and reduce costs. Although the Health and Social Care Act 2012 (Great Britain. Health and Social Care Act 2012. London: The Stationery Office; 2012) requires both competition and the collaboration needed to achieve care integration, the two are not always compatible. We conclude that competitive forces are dominant in driving the current uses of PLICSs. Future research should interrogate the use of PLICSs in New Care Models - Vanguard Sites (NHS England. New Care Models - Vanguard Sites. NHS England; 2015) and initiatives to deliver the 'Five Year Forward View' (Monitor and NHS England. Reforming the Payment System for NHS Services: Supporting the Five Year Forward View. London: Monitor; 2015). Funding: The National Institute for Health Research Health Services and Delivery Research programme.